(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Designing a human resource management (HRM) model for the future agile chemical industry within the framework of administrative systems requires addressing several critical aspects. The model needs to foster flexibility, responsiveness, and innovation while respecting cultural and regulatory contexts. Here is a structured outline for developing such a model. Chemical industries and systems are among the most important industries in the world..